The "Real Environment" Quantification of Surface Hydrophobicity of Differently Stabilized Nanocrystals as Key Parameter for Organ Distribution. Issue 1 (November 2014) - Staufenbiel, Sven; Keck, Cornelia M.; Müller, Rainer H.; Lendlein, Andreas; Domb, Abraham J.
Summary The surface hydrophobicity of nanoparticles is one factor determining blood protein adsorption after intravenous administration, thus the organ distribution. Hydrophobic surfaces lead to opsonization and uptake by the liver macrophages, when hydrophilic nanoparticles avoid this and can circulate in the blood. To predict, at least to a certain degree, the in vivo distribution, the surface hydrophobicity needs to be measured and quantified. Methods need to be used which quantify hydrophobicity of nanoparticles in liquid environment similar to the body situation (= real environment), not using e.g. dry methods from tabletting. Different of those methods are mentioned in this work. In the present study the hydrophobicity of differently coated azithromycin nanocrystals was analyzed with hydrophobic interaction chromatography (HIC) and aqueous two‐phase partitioning (TPP). Investigated stabilizers were Poloxamer 188, Poloxamer 407, caprylyl/capryl polyglucoside (Plantacare® 810), decyl polyglucoside (Plantacare® 2000), polyethylene glycol (PEG)‐20 sorbitan monooleate (Tween 80) and tocopheryl polyethylene glycol succinate. HIC results revealed that coating with PEG free Plantacares leads to more hydrophobic surfaces (e.g. Plantacare 2000 retention time (tr) = 17.0 ± 1.9 min and tr = 6.5 ± 0.1 min for Tween 80), when also an increase of the amount of polypropylene glycol (PPG) in the Poloxamers lead to a stronger retention. Furthermore, PEG containing samples were analyzed by TPP whereby HIC results could be confirmed. Additionally, TPP showed differences between stabilizers having only 1 PEG chain and stabilizers with more than 1 PEG chain. In perspective, these stabilizers leading to a low hydrophobicity are promising candidates for further in vivo studies due to a decreased opsonization.